The complete mitochondrial genome of North Island brown kiwi (Apteryx mantelli) - Jia Liu; Qing-xia Ding; Li-zhi Gao (Mitochondrial DNA. Part B. Resources, 2017)
Here, we report the complete mitochondrial genome sequence of North Island brown kiwi(Apteryx mantelli). The genome is found to be 16,694 bp in length and has a base composition of A (30.74%), G (13.46%), C (26.50%), and T (29.30%). Similar to other Apteryx species, it contains a typically conserved structure including 13 protein-coding genes, 2 rRNA genes, 1 control region (D-loop), and 22tRNA genes. The proportion of coding sequences with a total length of 11,431 bp is 68.47%, which encodes 3776 amino acids. All protein-coding genes started with Met, and ND2, COX2, and COX3 ended by TAA as a stop codon. The lengths of 12S ribosomal RNA and 16S ribosomal RNA are 973 bp and 1596 bp, respectively. The length of control region is 1112 bp, ranging from 15,583 bp to 16,694 bp. The complete mitochondrial genome sequence provided here would be useful for further understanding the evolution of ratite and conservation genetics of A. mantelli.